Detection of Echinococcus granulosus and Echinococcus ortleppi in Bhutan. Issue 2 (April 2017) - Thapa, Nirmal Kumar; Armua-Fernandez, Maria Teresa; Kinzang, Dukpa; Gurung, Ratna B.; Wangdi, Phuntsho; Deplazes, Peter
Abstract: In this pilot study, fecal samples were collected from community dogs around slaughterhouses and from the city of Thimphu ( n  = 138) as well as from carnivores in the forest area around a farm in Bhutan ( n  = 28). Samples were analyzed microscopically for the presence of taeniid eggs by the floatation and sieving method. Further molecular analyses of 20 samples of community dogs positive for taeniid eggs confirmed 10 Echinococcus granulosus sensu lato and one Taenia hydatigena case. From 14 environmental fecal samples from the forest area positive for taeniid eggs, one contained E. granulosus s.l., six T. hydatigena and one Taenia taeniaeformis DNA. In the remaining samples considered positive for taeniid eggs, no molecular confirmation could be achieved. Additionally, Echinococcus cysts were collected from locally slaughtered cattle and imported cattle organs. Seven Echinococcus cysts (one fertile) from the local animals and 35 (four fertile) from imported cattle organs were confirmed as E. granulosus (G1–3) by PCR/sequencing. One Echinococcus cyst each from a local animal and from an imported cattle organ (both fertile) were confirmed to be Echinococcus ortleppi (G5). Sterile Echinococcus cysts were also collected from local yaks ( n  = 10), and all revealed to be E. granulosus (G1–G3). Hospital records of cystic echinococcosis in humans and the presence of Echinococcus spp. in dogs and ungulates indicate the existence of local transmission for both E. ortleppi and E. granulosus in Bhutan. Graphical abstract: Highlights: Local transmission of Echinococcus granulosus and E. ortleppi in Bhutan was detected. Urban and rural community dogs could play a main role in Echinococcus spp. transmission.